Convective heat transport in a heat generating MHD vertical layer saturated by a non-Newtonian nanofluid: a bidirectional study. Issue 6 (18th June 2020) - Reddy, M. Gnaneswara; Vijayakumari, P.; Krishna, L.; Kumar, K. Ganesh; Prasannakumara, B.C
Abstract : Purpose: In this framework, the three dimensional (3D) flow of hydromagnetic Carreau nanofluid transport over a stretching sheet has been addressed by considering the impacts of nonlinear thermal radiation and convective conditions. Design/methodology/approach: Infinite shear rate viscosity impacts are invoiced in the modeling. The heat and mass transport characteristics are explored by employing the effects of a magnetic field, thermal nonlinear radiation and buoyancy effects. Rudimentary governing partial differential equations (PDEs) are represented and are transformed into ordinary differential equations by the use of similarity transformation. The nonlinear ordinary differential equations (ODEs), along with the boundary conditions, are resolved with the aid of a Runge-Kutta-Fehlberg scheme (RKFS) based on the shooting technique. Findings: The impact of sundry parameters like the viscosity ratio parameter ( β* ), nonlinear convection parameters due to temperature and concentration ( βT, βC ), mixed convection parameter ( α ), Hartmann number ( M 2 ), Weissenberg number ( We ), nonlinear radiation parameter ( N R ), and the Prandtl number (Pr) on the velocity, temperature and the concentration distributions are examined. Furthermore, the impacts of important variables on the skin friction, Nusselt number and the Sherwood number have been scrutinized through tables and graphical plots. Originality/value: The velocity distribution is suppressed by greater values of the Hartmann number. The velocity components in the tangential and axial directions of the fluid are raised with the viscosity ratio parameter and the tangential slip parameter, but these components are reduced with concentration to thermal buoyancy forces ratio and stretching sheet ratio.